Experiment and Literature: Enzyme Content of Fruit Waste-Based Eco Enzyme and Its Potential in Pollutant Reduction - Nurseha, Nida; Sari, Gina Lova; Ratnawati, Kania (Jurnal Biologi Tropis, 2025)
Indonesia faces serious challenges in managing domestic waste, especially organic waste, which constitutes the largest component of the total national waste generation. One innovative form of recycling is the fermentation of organic waste into eco enzymes, which are fermented liquids capable of producing various active enzymes such as protease, amylase, and lipase with broad ecological benefits. This study aims to observe the activity of protease, amylase, and lipase enzymes in eco enzyme solutions made from fruit waste, and compare the results with previous studies to analyze the potential application of eco enzymes as efficient, economical, and sustainable natural bioremediation agents. The fermentation process was carried out for 90 days, while enzyme activity was analyzed using spectrophotometry and titration methods. The results showed protease activity of 261 U/mL, amylase of 21.53 U/mL, and lipase of 3.46 U/mL. These values are relatively high compared to several previous studies, indicating that fruit waste is an effective substrate for eco enzyme production. Thus, it can be concluded that eco enzyme has great potential in reducing pollutants such as heavy metals, BOD, COD, TSS, and helping to stabilize pH, thereby playing an important role in the treatment of domestic waste and small-scale industrial waste. The recommendation from this study is the need for further research related to the optimization of substrate composition.